2024
DOI: 10.1371/journal.pone.0298930
|View full text |Cite
|
Sign up to set email alerts
|

Integrating microbial abundance time series with fermentation dynamics of the rumen microbiome via mathematical modelling

Mohsen Davoudkhani,
Francesco Rubino,
Christopher J. Creevey
et al.

Abstract: The rumen represents a dynamic microbial ecosystem where fermentation metabolites and microbial concentrations change over time in response to dietary changes. The integration of microbial genomic knowledge and dynamic modelling can enhance our system-level understanding of rumen ecosystem’s function. However, such an integration between dynamic models and rumen microbiota data is lacking. The objective of this work was to integrate rumen microbiota time series determined by 16S rRNA gene amplicon sequencing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…The inclusion of all the IPs in the interactions impacting variation suggests that the model should be improved to better characterize the interactions. The incorporation of microbial genomic knowledge is expected to improve the representation of rumen microbial fermentation in mathematical models (Davoudkhani et al, 2024; Muñoz-Tamayo et al, 2023). The first feed distribution of the low AT treatment showed that the variation of can also be only impacted by the interactions between IPs, highlighting the importance of quantifying the interactions between IPs in SA approaches used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of all the IPs in the interactions impacting variation suggests that the model should be improved to better characterize the interactions. The incorporation of microbial genomic knowledge is expected to improve the representation of rumen microbial fermentation in mathematical models (Davoudkhani et al, 2024; Muñoz-Tamayo et al, 2023). The first feed distribution of the low AT treatment showed that the variation of can also be only impacted by the interactions between IPs, highlighting the importance of quantifying the interactions between IPs in SA approaches used.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of all the IPs in the interactions impacting 𝑞 CH 4 ,g,out variation suggests that the model should be improved to better characterize the interactions. The incorporation of microbial genomic knowledge is expected to improve the representation of rumen microbial fermentation in mathematical models (Davoudkhani et al, 2024;Muñoz-Tamayo et al, 2023).…”
Section: Rate Of Methane Productionmentioning
confidence: 99%